THE EFFECT OF COOPERATIVE SCRIPT METHOD TOWARDS STUDENTSâ INTEREST IN READING - Nurhafani, Nurhafani (Journal of Languages and Language Teaching, 2016)
This thesis intended to find out the effect of Cooperative Script method toward studentsâ interest in reading comprehension and correlation between interest and reading comprehension. All of students in eighth grade at SMP Muhammadiyah Mataram were 17 students. All of eighth grade students used as sample. Students as samples treated by Cooperative Script. First, the students were given pre-test, after they were given post-test in form test and questionnaire. The result of studentsâ interest showed that the mean score pre-questionnaire was 63,17 and the mean score of post-questionnaire wasÂ  77,73. The standard deviation of pre-questionnaire was 125,59 and the standard deviation of post-questionnaire 173,88. Another result obtained through the analysis of the data was the value of t-test was 3,797 and t-table which was 2,120. It indicated that the value of t-test was higher than the value of t-table. Moreover r-count showed 0,634 and r-table was 0.482. It meant, r-count was higher than r-table 0,634 (>0.482). It concluded Cooperative Script had positive effect toward studentsâ interest in reading comprehension and the data showed there was a correlation between interest and reading comprehension.